The development of collective transport modes share in total inland passenger transport performance of selected European countries from the perspective of sustainable city logistics - Chocholáč, Jan; Sommerauerová, Dana; Hyršlová, Jaroslava; Kučera, Tomáš; Hruška, Roman; Machalík, Stanislav (Kaunas University of Technology, 2019)
Sustainable development of cities is based on three pillars – economic pillar, environmental pillar and social pillar. Emphasis is placed on the environmental pillar from the perspective of city logistics, because the transport is an important producer of emissions and associated negative environmental impacts. An important role in terms of negative environmental impacts is represented by passenger car transport, because passenger car transport produces more emissions per capita than collective transport. Collective transport modes represented by buses, coaches, trolley-buses and trains are more environmentally friendly than using individual passenger car transport. EUROSTAT defined seventeen sustainable development goals and groups of indicators. This article is focused on the indicator “Share of busses and trains in total passenger transport” which measures the share of collective transport modes in total inland passenger transport performance, expressed in passenger-kilometres. The aim of the article is to analyse the development of this indicator of selected European countries between 2007 and 2016 from the perspective of sustainable city logistics.
Vývoj podílu veřejné hromadné dopravy na celkovém vnitrozemském přepravním výkonu osobní dopravy ve vybraných evropských státech z hlediska udržitelné city logistiky
Keywords: sustainable development; sustainable development indicators; collective transport modes; sustainable city logistics; udržitelný rozvoj; indikátory udržitelného rozvoje; veřejná hromadná doprava; udržitelná city logistika